2020
DOI: 10.1044/2020_persp-20-00087
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Post-Swallow Residue in Healthy Aging

Abstract: Purpose Reports are mixed on whether post-swallow residue increases with age. This question was investigated using a quantitative measure of residue in a large cohort of healthy adults. It was hypothesized that post-swallow residue would differ between younger and older healthy adults, and significantly increase in individuals ≥ 80 years. Method In this observational study, 275 healthy volunteers aged 18–99 years underwent videofluoroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Since the California videos pre‐dated IDDSI, the barium was not tested but was presumed to be thin (Barosperse diluted to 45% concentration). Although the concentration of the California barium was slightly stronger (45% vs. 32% w/v), results between the research sites have been previously analyzed and not found to differ significantly, t (216.86) = 0.29, p = 0.77, 8 and were therefore merged.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Since the California videos pre‐dated IDDSI, the barium was not tested but was presumed to be thin (Barosperse diluted to 45% concentration). Although the concentration of the California barium was slightly stronger (45% vs. 32% w/v), results between the research sites have been previously analyzed and not found to differ significantly, t (216.86) = 0.29, p = 0.77, 8 and were therefore merged.…”
Section: Methodsmentioning
confidence: 91%
“…Other measures included the Penetration-Aspiration Scale (PAS) 9 -an ordinal scale of depth and response to airway invasion and pharyngeal timing and displacement parameters as described by Leonard and colleagues. 6,8,10,11 including the following: pharyngeal constriction ratio (PCR), pharyngoesophageal segment (PES) opening (PESmax), maximum hyoid displacement (HMax), hyoid-larynx displacement (HL) and Bolus Clearance Ratio (BCR).…”
Section: Pharyngeal Shorteningmentioning
confidence: 99%
“…Consistently reported age effects include increased swallow reaction, bolus transit, and UES opening times, and pressure changes at the UES and LES [8,10,11]. Swallowing compensatory strategies may be spontaneously adopted, such as dose metering (dividing a bolus in the mouth so that the quantity swallowed is smaller), clearing oral residue, and taking smaller sips or mouthfuls [12].…”
Section: Introductionmentioning
confidence: 94%